KNOWLEDGE AND ATTITUDE OF NURSES ABOUT MEDICATION ERROR IN THE EMERGENCY DEPARTMENT AT TERTIARY CARE HOSPITAL - FATIMA, SS; SADDIQUE, H; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Medication errors are a significant concern in healthcare, particularly in emergency departments where high workloads and resource limitations increase the risk of errors. Nurses play a critical role in minimizing medication errors through proper knowledge and positive attitudes toward error reporting. However, in Pakistan, the prevalence of medication errors remains high, and little is known about the knowledge and attitudes of nurses in this context. Objective: To assess the knowledge and attitudes of nurses regarding medication errors in emergency departments of tertiary care hospitals. Methods: A descriptive cross-sectional study was conducted among 135 nurses using a validated questionnaire. Data were analyzed using SPSS version 26, with descriptive statistics summarizing knowledge and attitude scores. Results: All participants (100%) identified medication errors as a significant preventable cause of harm. While most nurses demonstrated moderate knowledge, 54.1% expressed reluctance to report errors due to fear of being labelled troublemakers, and 76.3% agreed that fear of blame influenced their decision to avoid reporting errors. Nearly half (49.6%) were neutral regarding the impact of managerial reactions on their willingness to report errors. Conclusion: Despite moderate knowledge, negative attitudes toward reporting medication errors persist among nurses. Addressing these issues through education, policy reform, and fostering a culture of safety and accountability is essential for improving patient safety in Pakistan’s emergency departments.